Komite Audit, Kualitas Audit dan Audit Tenure dalam Meningkatkan Kekuatan Integritas Laporan Keuangan: Studi Empiris pada Perusahaan BUMN Tahun 2021-2023 - Mega Juwita Saragih Simarmata; Khomsiyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research focuses on state-owned companies in 2021-2023 to evaluate the role of the audit committee, audit quality, and auditor tenure to improve the integrity of financial reports. The integrity of financial reports is a crucial aspect in business and finance because reliable and accurate reports are the basis for stakeholders in making economic decisions. This study was motivated by several cases in state-owned companies, such as PT Garuda Indonesia and PT Asuransi Jiwasraya, which showed dishonesty in financial reporting. This analysis is aimed at assessing the professionalism of the audit committee and the independent monitoring system on the performance taken for this research is secondary. With analysis tools using SPSS version 25. management to produce quality audits. Data a The research methodology involves analyzing data from 36 samples of state-owned companies using classic assumption tests, such as normality tests, multicollinearity tests, autocorrelation tests, and heteroscedasticity tests. The results of the analysis state that the audit committee variable, audit quality has a significant impact on the integrity of financial reports and audit tenure has no significant effect on the integrity of financial reports. The contribution of this analysis is the importance of the audit committee's role in improving the integrity of financial reports as reflected in effectiveness in a transparent and accountable manner, the selection of auditors who have a reputation and high competence ensures reliable financial reports, provides insight into the impact of long-term relationships between auditors and clients on the integrity of financial reports.